2008
DOI: 10.1007/s10834-008-9113-z
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood and Commitment to the Legal Profession: Are Mothers Less Committed than Fathers?

Abstract: Career commitment, Parenthood, Professionals, Work–family balance, Support,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Women are generally viewed as less committed to their careers than men, and studies show that women in medicine are more likely to leave the profession and do so sooner than men, and are less inclined to join professional organizations (Burton and Wong, 2004;Wallace, 2008). Because large numbers of women have entered the professions more recently, women in the professions average less experience than their male counterparts (Reskin, 2003;Wallace and Kay, 2012).…”
Section: Gender Work and Family Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are generally viewed as less committed to their careers than men, and studies show that women in medicine are more likely to leave the profession and do so sooner than men, and are less inclined to join professional organizations (Burton and Wong, 2004;Wallace, 2008). Because large numbers of women have entered the professions more recently, women in the professions average less experience than their male counterparts (Reskin, 2003;Wallace and Kay, 2012).…”
Section: Gender Work and Family Involvementmentioning
confidence: 99%
“…This interpretation is challenged, however, by the finding that mothers receive less emotional and informational support than women without children, which is consistent with the family involvement hypothesis. The literature suggests that contemporary cultural beliefs assume that women with family responsibilities bring less effort to their work, and are less motivated and productive because they are either saving their energy for their home time or they have no energy left for work after meeting their home responsibilities, despite empirical evidence that has shown otherwise (Bielby and Bielby, 1988;Voydanoff, 2004;Wallace, 2008;Young and Wallace, 2009). As well, Correll et al's (2007) experimental study examining status-based discrimination mechanisms found that mothers are rated as less competent and committed to paid work than non-mothers and they are consequently discriminated against in terms of hiring and salary decisions.…”
Section: Gender Work and Family Involvementmentioning
confidence: 99%
“…This cultural norm exists in tension with another widely held normative belief that the "ideal worker," particularly a professional, demonstrates intensive effort on the job and is unencumbered by outside demands (Correll et al 2007;Williams 2001). This perceived tension between incompatible cultural schemas leads evaluators, perhaps unconsciously, to expect mothers to be less competent and less committed to their jobs (Blair-Loy 2003;Correll et al 2007;Kmec 2011;Wallace 2004). Conversely, mothers who are highly successful, particularly in male-typed jobs, may be viewed as competent and committed but also seen as more interpersonally hostile, less warm and likable, and as a result more likely to be excluded and denied salary increases, promotions, and other rewards (Benard and Correll 2010).…”
Section: Group Status and Expectations Of Competence And Givingmentioning
confidence: 99%
“…Similarly, colleagues may prefer to share valuable information and lend emotional support to those individuals they perceive as competent and deserving of their professional support. EST further hypothesizes that in the context of time-demanding professional work such as law, mothers are perceived to be torn by their responsibilities to dependent children and less committed to the profession (Wallace 2008). These unfavorable, though often unconscious, impressions of women lawyers and lawyers who are mothers, will lead coworkers to extend support, through information sharing and encouragement, more often to male lawyers, colleagues they perceive to be more deserving and dedicated professionals.…”
Section: Group Status and Expectations Of Competence And Givingmentioning
confidence: 99%
“…First, the sample represents educationally and financially elite professionals with demanding work schedules. Professionals, such as lawyers, must devote substantial time and energy to their work (Coltrane, 2004;Wallace, 2005), and women who have entered this demanding, high-status, male-dominated field may be exceptionally committed ''career women'' (Epstein, 1993;Wallace, 2008).…”
Section: Introductionmentioning
confidence: 99%